INTEGRATING BILATERAL APPROACH TO COMBAT COMBINED IIMPACTS OF HERITAGE TOURISM AND CLIMATE CHANGE (International Association of Biologicals and Computational Digest, 2022)
.Climate change and sustainability does not prominently manifold with respect to tourism industry within the environmental, economic and tourism policy agendas of developing countries. Evidences shows that developing countries are most vulnerable entities to the climate change. Tourism is married to good climate conditions, any attempt to divorce them could lead to danger. Tourism is considered as one of the fast-growing sectors for economy of India as it occupies 9.4% share in annual national gross development product (GDP). Since 1990s heritage is most important as well as fastest growing entity of tourism. Rankivaav (Queen’s stepwell) N23 51 32 E72 66 is a world heritage site of The United Nations Educational, Scientific and Cultural Organization (UNESCO) attracts many national and international tourists. As tourism is a growing sector it is essential to identify its promising impacts on climate change. To encounter this consequence, we tried to figure out emission of greenhouse gases by using socio-economic methods as well as establishment of the relations between sustainable development, tourism and climate change. This research suggests certain conclusion of possible relevance to climate change and sustainable developments that includes all aspects of tourism, sustainability development goals, carbon footprint, adaptation and mitigation measures, which eventually lead to the critical importance of alternative development path and assumptions about the reference case.
Keywords: Climate change, Heritage tourism, sustainability, carbon footprint.